1989
DOI: 10.1002/oms.1210240216
|View full text |Cite
|
Sign up to set email alerts
|

Ethylation of ethanol in the gas phase

Abstract: Etbylation of Ethanol in the Gas PhaseIn the gas phase, alkyl halides RX lead either to alkylation' or protonation reactions. ' The reagent in these processes (RX", R+ or R-X+-R) can often be determined by ion cyclotron resonance but not so easily under chemical ionization conditions. In this work, CH, CD, I and CD, CH, I have been used to determine the mechanism of the ethylation of ethanol by CH, CH, I in the source of a mass spectrometer (VG ZAB 2F).In the ion source, equimolecular quantities of C, H, OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 4 publications
4
21
0
Order By: Relevance
“…1c- Our results indicate that H atom migration from both the ␣ and ␤ positions of the side chain occurred in the ethylene elimination reaction, as reported previously [7,8]. In the mass spectrum of C 6 D 5 CD 2 CH 3 , the H/D exchange was substantial for both the benzenium-type ions and the ethylbenzenium-type ions, as was the case for C 6 D 5 CD 2 CD 3 ; whereas H/D exchange seems to have been suppressed for C 6 H 5 CH 2 CD 3 and C 6 H 5 CD 2 CH 3 .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…1c- Our results indicate that H atom migration from both the ␣ and ␤ positions of the side chain occurred in the ethylene elimination reaction, as reported previously [7,8]. In the mass spectrum of C 6 D 5 CD 2 CH 3 , the H/D exchange was substantial for both the benzenium-type ions and the ethylbenzenium-type ions, as was the case for C 6 D 5 CD 2 CD 3 ; whereas H/D exchange seems to have been suppressed for C 6 H 5 CH 2 CD 3 and C 6 H 5 CD 2 CH 3 .…”
Section: Resultssupporting
confidence: 86%
“…Fig. 4 shows a plot of i vs. ␣ 1 ; the data obtained in the present study are shown as filled circles with error limits, and data from previous studies [7,8] are also plotted. Our data overlapped with the data for CH 4 , CD 4 , and H 2 O CI, but the data for H 2 and D 2 CI gave higher ␣ 1 values and lower i values.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In metastable protonated ethylbenzene 1 the permutation of the aliphatic hydrogens prior to C2H4 loss is incomplete but observed. This is in agreement with isomerization via 1,2-hydrogen shift in the n-complex [c6& C,H:] , 34 but a concerted pathway cannot be discarded. Metastable protonated n-propylbenzene 2 isomerizes irreversibly but completely to protonated isopropylbenzene 3 prior to d i s s~c i a t i o n ,~~,~~ while for the less energetic metastable ion 3 two interconverting complexes [C6H, s-C,H;] and [C,H; C,H,] are intermediates in the reaction process.…”
supporting
confidence: 82%